Determinants of early postnatal care attendance in Uganda: further analysis of the 2016 demographic and health survey - Ndugga, Patricia; Namiyonga, Noor Kassim; Sebuwufu, Deogratious (DHS Working Papers No. 148, 2019)
Background: The first two days after childbirth present the highest risk of dying for a mother. Providing postnatal care within the first two days after childbirth can help avert maternal mortality because it allows early detection of problems that could result in adverse maternal health outcomes. Unfortunately, knowledge of the uptake of early postnatal care (EPNC), which is imperative for informing policies aimed at reducing maternal mortality, remains low in Uganda. Therefore, the purpose of this study is to investigate the determinants of early postnatal care attendance among Ugandan women of reproductive age. Methods: This study was based on nationally representative data from the 2016 Uganda Demographic and Health Survey (UDHS). The study sample comprised 5,471 women of reproductive age 15–49 who delivered a child in the 2 years preceding the survey. We used logistic regression to identify factors associated with use of early postnatal care. Andersen’s Behavioral Model of health services utilization guided the selection of independent variables. Results: Our findings showed that 50% of mothers used EPNC services for their most recent delivery in the 2 years preceding the survey. Women’s residence, education level, religion, wealth status, marital status, occupation, antenatal care (ANC) attendance, place of delivery, birth order, perceived accessibility of health facilities, and access to mass media messages were associated with greater use of EPNC. Women in urban areas were more likely to use EPNC than women in rural areas, at 63% versus 46%. Nearly two-thirds of the women with secondary education or higher (64%) received EPNC compared with less than half of women with no education (47%) and women with a primary education (44%).Receipt of EPNC was more common among women who attended at least four ANC visits for their most recent birth, at 54%, versus 43% among women who did not receive the recommended four or more ANC visits. The percentage of women receiving EPNC was much higher among women who delivered at a health facility, either a public facility (63%) or private facility (65%), versus only 9% among women who delivered at home. Multivariate analysis showed that delivery at a health facility was the most important determinant of early postnatal care attendance. Even so, the fact that only about two-thirds of women who delivered at a health facility received early postpartum care shows substantial room for improvement. Conclusion: To increase mothers’ use of EPNC services and improve maternal survival in Uganda, policies and programs could promote and strengthen health facility delivery and ensure that EPNC services are provided to all women before discharge. Interventions should target women who deliver at home, women who attend fewer than four ANC visits, and women with a primary education.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The DHS Working Papers series is a prepublication series of papers reporting on research in progress that is based on Demographic and Health Surveys (DHS) data. This study was carried out with support provided by the United States Agency for International Development (USAID) through The DHS Program (#AIDOAA-C-13-00095). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government.